Representasi Maskulinitas Pria dalam Iklan Kahf Edisi Life is a Journey #JalanYangKupilih (Analisis Semiotika Roland Barthes) - Utari, Maulida Dyah Nur; Amy Istiqlala Sophia Hikmah (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
The concept of masculinity in men is typically associated with strong, brave physical traits, a disregard for  appearance, and an adventurous spirit. Oftentimes, men feel constrained by this masculinity stereotype, leading them to overlook self-care. This stereotype has made men less inclined to consider using skincare products as they are seen as feminine and not in line with societal norms. However, the meaning of masculinity has shifted due to media influence conveying messages from various perspectives, including advertisements from brands. This shift is also influenced by the broader and more open-minded thinking of the audience. Masculinity is no longer confined to specific traits, allowing skincare brands targeting men to effectively convey their messages to the audience. This descriptive qualitative research delves into the meanings contained within an advertisement from the brand Kahf, specifically focusing on the "Life is a Journey #JalanYangKupilih". The analysis method employs Roland Barthes' semiotic theory and a constructivist paradigm, where reality is formed and constructed, interpreted differently by individuals based on their experiences, preferences and environmental background. The research problem centers on elucidating the meanings of signifiers (Denotative), signifieds (Connotative), and myths (Mythic) in the "Life is a Journey #JalanYangKupilih" ad on YouTube from the perspective of masculinity representation. Triangulation of data sources is also utilized for data validity. The research findings indicate that the "Life is a Journey #JalanYangKupilih" ad by Kahf provides a new meaning to the current representation of masculinity, where skincare products have become a necessity for men, successfully dispelling negative stereotypes. Roland Barthes' semiotic theory reveals three layers of meaning: Denotative, Connotative, and Mythic. Each of these meanings reflects representations of masculinity in various scenes within the Kahf brand advertisement. This reflects a shift in the meaning or myth of masculinity in men's appearance, aligning with the evolution of modern preferences. Keywords: Masculinity, Representation, Semiotics, Advertising